Characteristics of Light Plains North of Mare Frigoris - Koehler, U.; Neukum, G. (1997)
The nature of lunar light plains is not yet fully understood. Although there are unambiguous signs of an origin related to the ejecta of the major impacts, especially of the Imbrium and Orientale event, crater-frequency measurements show that several light plains are younger than ejecta blankets from the Orientale basin, supposedly the last basin-forming impact on the Moon. In addition, results from multispectral image analysis at least do not exclude the idea on an involvement of volcanic components during the formation of theses plains, thus supporting an origin independent from the Orientale and Imbrium event. This may also involve cryptomaria,as probably exposed at the dark-halo crater Gaertner D. Data sets recently gained with modern digital multispectral VIS-NIR imaging systems of areas poorly visible from the Earth un moderate (Galileo, E/M 2) and high resolution (Clementine) proved to be useful for investigations of light plains north of Mare Frigoris, where towards the north pole a great concentration of light plains can be found. SOme of the identified areas have been analyzed with photogeologic methods, the results being discussed in the context of their respective geologic setting and its evolution. Crater counts have been performed and used to derive absolute ages. Where possible,multispectral information has been added to shed new light on the formation of light plains: Because of the detection of both highland and mare spectral signatures a uniform process for the formation of light plains seems unlikely.